2007
DOI: 10.1007/s10984-007-9023-2
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of science teachers’ interpersonal behaviour in secondary schools: Development of a Turkish version of the Questionnaire on Teacher Interaction

Abstract: The purpose of the study was to investigate the reliability and validity of a Turkish adaptation of an existing instrument for measuring teacher interpersonal behaviour. The Questionnaire on Teacher Interaction (QTI) maps teacher behaviour in terms of two dimensions: Influence (Dominance-Submission) and Proximity (Cooperation-Opposition). A sample of 674 students from 24 classes (Grades 9-11) of experienced teachers in two Turkish secondary schools participated in the study. Development of the instrument invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 20 publications
5
57
0
9
Order By: Relevance
“…This version was initially also applied in Australia and was then revised into a 48-item selection for the Australian context (Wubbels 1993). This Australian version of the QTI was then translated into several languages and applied in various countries such as Singapore (Goh and Fraser 1998), Brunei (Scott and Fisher 2004), Turkey (Telli et al 2007), Indonesia (Maulana et al 2012) and Italy (Passini et al 2015). Although these later translations could have had the goal of achieving to the original QTI parallel measures, most of them used translation procedures only.…”
Section: Questionnaire On Teacher Interaction (Qti)mentioning
confidence: 99%
See 3 more Smart Citations
“…This version was initially also applied in Australia and was then revised into a 48-item selection for the Australian context (Wubbels 1993). This Australian version of the QTI was then translated into several languages and applied in various countries such as Singapore (Goh and Fraser 1998), Brunei (Scott and Fisher 2004), Turkey (Telli et al 2007), Indonesia (Maulana et al 2012) and Italy (Passini et al 2015). Although these later translations could have had the goal of achieving to the original QTI parallel measures, most of them used translation procedures only.…”
Section: Questionnaire On Teacher Interaction (Qti)mentioning
confidence: 99%
“…the specific position of an item on the interpersonal circle). As noted by Telli et al (2007), if only translation and back-translation procedures are be applied, scale reliability might appear good, but it is questionable whether such a translation would be conceptually comparable to the original Dutch and English versions. Hence, when adapting the QTI to another language, it is essential to adapt to the local context by considering the position of the items on the circle, and thus to create a version conceptually parallel with the IPC-T.…”
Section: Questionnaire On Teacher Interaction (Qti)mentioning
confidence: 99%
See 2 more Smart Citations
“…This variety can partly be explained by student-related factors that affect perceptions (such as gender, ethnic background, age), class and school factors (such as school type, denomination, location, class size, grade level, subject matter) and also teacher factors (gender, ethnic background, age, experience) Fisher et al 2006;Fraser 2007;Levy et al 2003;Wubbels et al 2006). Research has also shown that differences between classes in terms of the learning environment that remain after taking into account all of the aforementioned factors are systematic and can be captured in terms of classroom profiles or typologies (den Rickards et al 2005;Telli et al 2007b;Wubbels and Brekelmans 1998;Wubbels et al 2006;Wubbels and Levy 1993). Many of these profiles were established within one particular strand of learning environments research, namely, research on the teacher-student interpersonal relationship, and used one particular instrument to map this behaviour, the Questionnaire on Teacher Interaction (QTI; Wubbels et al 1985).…”
Section: Introductionmentioning
confidence: 99%